Rickets in the Middle East: Role of environment and genetic predisposition - BEREKET, ABDULLAH (ENDOCRINE SOC, 2008)
Context: The Middle East has a high incidence of rickets, and it is also common in Europe-dwelling children of Middle Eastern origin. Objective: The objective of the study was to explore the mechanisms leading to rickets in children of the Middle East. Design and Setting: We conducted a prospective study in 98 rachitic and 50 controls (aged 6 months to 4 yr) from university and community outpatient hospitals in Egypt and Turkey. Main Outcome Measures: We collected epidemiological, maternal, nutritional, radiographic, and biochemical parameters; markers of bone turnover; and vitamin D receptor (VDR) gene polymorphisms. Results: Epidemiological factors had a key role in pursuit of rickets; Egyptian and Turkish patients had lower (P < 0.01) dietary calcium intake than controls and the recommended dietary intakes, and serum 25-hydroxyvitamin D levels were reduced in patients, the difference with controls being significant (P < 0.001) only in Turkey, although rickets was more severe in Egypt as determined by the x-ray score (P < 0.05). In Turkey, the F VDR allele frequency was significantly (P < 0.05) increased in patients. The BB VDR genotype was associated with lower serum 25-hydroxyvitamin D levels in both patients and controls and with severity of rickets. Conclusions: In Turkey most patients had vitamin D deficiency, whereas in Egypt they had mostly calcium insufficiency combined with vitamin D deficiency. In this environ, VDR genotypes may predispose to rickets by increased frequency of the F allele. The unique environs and genetic predisposition have to be accounted for in the design of preventive measures, rather than using European or American recommended dietary intake for calcium and vitamin D.
Keywords: VITAMIN-D-RECEPTOR; BONE-MINERAL DENSITY; NUTRITIONAL RICKETS; D DEFICIENCY; DIETARY CALCIUM; PARATHYROID-HORMONE; CHILDREN; POLYMORPHISM; 25-HYDROXYVITAMIN-D; PREVALENCE